+0  
 
0
225
3
avatar

 

Please Help!

 Mar 13, 2018
 #1
avatar+98123 
+1

Here's the first two

 

lim  e^x    =         e^(-1)  ≈    0.368

x → - 1

 

lim     ln x    =      ln e    =  1  

x → e

 

 

 

cool cool cool

 Mar 13, 2018
 #2
avatar+10074 
+1

Here is the third one

laugh

 Mar 13, 2018
edited by Omi67  Mar 13, 2018
 #3
avatar
0

Happy 4th anniversary on the site my man... You have helped me out with so many problems CPhill I really appreciate you and keep up the good work

 Mar 13, 2018

14 Online Users

avatar
avatar